Evaluation of the bioactivity and stability of gold nanoparticles conjugated with Os-C(W5) against Candida albicans biofilms - Bester, Megan J. (University of Pretoria, 2024)
Dissertation (MSc (Anatomy))--University of Pretoria, 2023.